Problematika Pesantren dan Lembaga Pendidikan Islam - Taufiqurrahman, Taufiqurrahman; Kurniawan, Ilham; Hakim, Lukmanul; Abdullah, Abdullah; Rohman, Abdul (Lembaga Yasin AlSys, 2026)
Pesantren, as the oldest and most distinctive Islamic educational institutions in Indonesia, play a central role in shaping character, morals, and the preservation of Islamic values, yet in the midst of modernization and globalization they face various critical problems. This study aims to identify the main challenges faced by pesantren and other Islamic educational institutions, including limited resources (infrastructure, technology, and funding), the relevance of the curriculum in responding to labor market demands, and the need for more dynamic and adaptive educational methodologies. Using a qualitative-descriptive approach based on literature study, this analysis shows that pesantren are required to achieve a balance between the tradition of Kitab Kuning and modernity in the form of mastery of general sciences and technology. The suggested solutions include integrating a comprehensive curriculum that combines Islamic studies with mathematics, science, ICT, and languages; developing problem-based and interactive learning methodologies; and strengthening the economic self-reliance of pesantren. These adaptation efforts are crucial for enabling pesantren to maintain their scholarly identity while making a significant contribution to producing cadres who are mutafaqqih fiddin and competitive in the contemporary era.